2007
DOI: 10.1016/j.domaniend.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Differences between primiparous and multiparous dairy cows in the inter-relationships between metabolic traits, milk yield and body condition score in the periparturient period

Abstract: During the early postpartum period dairy cows mobilize fat and muscle to support lactation. This is associated with alterations in blood metabolite and hormone profiles which in turn influence milk yield and fertility. This study developed models to determine how metabolic traits, milk yield and body condition score were inter-related at different times in the periparturient period and to compare these relationships in primiparous (PP, n=188) and multiparous (MP, n=312) cows. Data from four previous studies wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
256
7
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(314 citation statements)
references
References 50 publications
37
256
7
14
Order By: Relevance
“…After parturition, plasma NEFA concentrations were higher in multiparous than primiparous goats. A similar result is observed in dairy cows (Wathes et al, 2007). This was possibly due to the fact that in the multiparous group there was a greater number of goats that gave birth to triplets of kids in comparison to the primiparous group.…”
Section: Plasma Metabolitessupporting
confidence: 71%
See 1 more Smart Citation
“…After parturition, plasma NEFA concentrations were higher in multiparous than primiparous goats. A similar result is observed in dairy cows (Wathes et al, 2007). This was possibly due to the fact that in the multiparous group there was a greater number of goats that gave birth to triplets of kids in comparison to the primiparous group.…”
Section: Plasma Metabolitessupporting
confidence: 71%
“…Anyway, in primiparous goats, the negative correlation between insulin and NEFA suggests the role of insulin in the reduction of lipomobilization at the beginning of lactation. To justify this latter statement, it is important to consider that (due to the seasonality of the reproductive activity) at the time of first kidding goats are less mature than at the time of the following ones and so they need nutrients also for their own physical and physiological development (Shelton, 1978;Wathes et al, 2007). It is possible to hypothesize, therefore, that the higher levels of plasma insulin observed in primiparous goats compared to the multiparous ones soon after parturition acted as a metabolic strategy to limit both the mobilization of bodily reserves and the capture of nutrients by the lactating mammary gland, thus providing nutrients for whole body growth.…”
Section: Plasma Insulinmentioning
confidence: 99%
“…Greater milk production in older parity cows and the associated greater negative energy balance (Berry et al, 2006) may also be a contributing factor to increase prevalence of embryo/foetal death in these animals. Moreover, the bovine endocrine and immune system age rapidly; Wathes et al (2007) documented reduced levels of circulating IGF-1 and insulin in early lactation multiparous Holstein-Friesian dairy cows compared with early lactation primiparous Holstein-Friesian dairy cows. Such endocrine differences between parities are also likely to contribute to parity differences in reproductive performance.…”
Section: Paritymentioning
confidence: 99%
“…Different genotypes can alter the endocrine and metabolic profiles of the transition dairy cow under grazing condition [17] . Several studies reported periparturient changes of IGF-I blood concentration in cattle [18,19] . It has been reported significant associations between single nucleotide polymorphisms (SNPs) in IGF-I and production traits in Holstein-Friesian cattle [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the genomic DNAs were eluted in a volume of 100 毺L supplied elution buffer. The extracted DNA was diluted to a working concentration of [10][11][12][13][14][15][16][17][18][19][20] ng/毺L, and 2.4 毺L of it was used as a template in PCR.…”
Section: Introductionmentioning
confidence: 99%